The Comparison of the Effects of Attentional-Cognitive Load and Motor-Cognitive Load on Bimanual Coordination Performance - Alireza Farsi; Behrooz Abdoli; Maryam Kaviyani (University of Tehran, 2011)
The aim of this study was to compare the effects of cognitive-attentional and cognitive-motor load on the performance of bimanual coordination skill. 31 female students (mean age 25+2 years) from Shahid Beheshti University attending were selected voluntarily and divided randomly into three groups: single group (N=11), cognitive group (N=10) and cognitive-motor group (N=10). Single group participants performed bimanual coordination single task. Cognitive group participants performed bimanual coordination task simultaneously with number countdown task, and cognitive - motor participants performed bimanual coordination task simultaneously with feet reaction time task. Two hand coordination of Vienna test system was used to assess the performance of bimanual coordination task. One - way ANOVA and Tukey post hoc test were used to analyze data. Statistical significance level was p